P751 Perianal lesions in Crohn's disease: analysis of Epimad registry from 2007 to 2012. (25th January 2019) - Wils, P; Leroyer, A; Fumery, M; Fernandez Nistal, A; Bojic, D; D′Ambrosio, R; Sarter, H; Savoye, G; Gower-Rousseau, C; Pariente, B
Abstract: Background: Perianal lesions (PL) affect up to 30% of Crohn's disease (CD) patients in the first two decades after diagnosis and are associated with poor outcomes. Data concerning evaluation and clinical management of PL at diagnosis in prospective cohorts are scarce. Aims of the present study were to characterise CD patients with PL at diagnosis and describe their initial diagnostic and therapeutic management. Methods: All CD patients diagnosed between 2007 and 2012 were extracted from the Epimad Registry, a French multi-centre prospective registry. PL were defined by the presence of fistula or abscess at CD diagnosis. The following variables were described using a cross-sectional analysis: clinical examination, perianal MRI, echo-endoscopy, examination under general anaesthesia (GA) and medical and/or surgical management within the first 3 months after CD diagnosis. Associated factors with PL at CD diagnosis were identified using a logistic regression. Results: Among the 2906 patients with CD diagnosed from 2007 to 2012, 116 (4%) had PL at CD diagnosis. Forty-four per cent were women, the median age at diagnosis was 25 years (IQR: 19–39) and 45% had a previous history of PL. Ileocolonic CD (L3) was predominant in 51 patients (45%); one patient (1%) had only perianal involvement and 51% of patients presented rectal lesions. Patients could present one or more PL: 81% had fistula (including 12 rectovaginal fistulas) and 58% abscess; one patient (1%) had anal stenosis. An examination under GA was performed in 50% of patients, MRI in 34% of the patients and an echo-endoscopy in 1 case. Initial therapeutic management of CD: 63% of patients received antibiotics, 42% 5-ASA and 47% steroids. Twenty-seven per cent of patients received azathioprine, 29% anti-TNF therapy (90% infliximab) and 13 (12%) patients received a combination therapy. Surgery was performed in 64 patients (57%) with 41 abscess drainages, 25 seton drainages, 16 fistulotomy and 2 diverting ileostomy. Male sex ( p < 0.01), luminal fistulising phenotype ( p < 0.0001) and colonic location ( p = 0.01) were significantly associated with the presence of PL at CD diagnosis. Conclusions: In this large population-based study, the proportion of patients with PL at CD diagnosis was 4%. Male sex, fistulising phenotype, and colonic location were associated with the presence of PL at CD diagnosis. Surgery was performed in more than half of the cases. An immunosuppressant, an anti-TNF or a combination therapy were, respectively, prescribed in 27%, 29% and 12% of the cases, reflecting the current approach for treating CD patients with PL. Further exploration of the treatment options after CD diagnosis is warranted.